A polymeric piezoelectric micropump based on lamination technology - Truong, Thai-Quang (2014)
This paper presents the first micropumps assembled using polymeric lamination technology. Each pump consists of two 100 ?m thick, 10 mm diameter SU-8 discs; two 1.5 mm thick, 15 mm diameter polymethylmethacrylate (PMMA) discs; and one piezo disc. The SU-8 parts were fabricated by a two-mask polymeric surface micromachining process with silicon as the sacrificial material. Each SU-8 disc has one micro check valve. The valve is a 1 mm plate suspended on a compliant orthoplanar spring. The cross section of the spring beam has a dimension of 100 ?m × 100 ?m. The PMMA parts were machined from an extrusion PMMA sheet by CO2 laser. An off-the-shelf piezo bimorph disc worked as both actuator and pump membrane. The pump was assembled using adhesive bonding. The adhesive tapes were cut by the same laser system. Alignment pins were used in the assembly process. With a drive voltage of ?150 V the fabricated micropumps have been able to provide flow rates up to 2.9 ml min?1 and back pressures up to 1.6 m of water. The pump design and the polymeric technologies prove the feasibility of making more complex microfluidic systems based on the presented lamination approach.